Posture Correction for Juvenile Idiopathic Scoliosis Using Flexible Fabric Stretch Sensors - A, Brightline; Nair, Malavika; B, Priyanka; M, Prathisha; Suresh Chandra Kapali, B (International Journal of Engineering and Technology, 2018)
Our device is being designed to help the juvenile from age 3 to 10 suffering from idiopathic scoliosis, a vertebral deformity that is usually congenital or neuromuscular in nature. The disorder that causes an abnormal lateral curvature of the vertebral column is known as scoliosis. This device will alert the patient by the stimulus given to them whenever the curvature of the bend of spinal cord has reached the threshold value of spinal curve angle on comparing with predetermined value. The sensor used in this device is flexible and thereby can be fixed to the fabrics so that the patients can wear them regularly. By using this device continuously, we can train the patients to maintain good posture for their entire life.